Jute Felt for Noise Reduction: Understanding Effect of Pore Size Distribution. Issue 13 (1st December 2022) - Basu, Gautam; Datta, Mallika; Sengupta, Surajit; Nath, Devarun; Debnath, Sayandeep
ABSTRACT: Effect of pore size and its distribution on the noise reduction coefficient of jute felt were studied through capillary flow porometer and impedance tube. The inter-criteria correlation method was used to optimize the type of jute felts to obtain noise reduction coefficient of 0.5. The porometry study of the needle punched jute felt suggested the gradient pore structure of felt due to presence of needling induced inverted cone of pores within fibrous mass. The jute felt with an areal density 796.5 g/m 2 with mean pore diameter 60.32 µm offered optimum noise reduction coefficient of 0.5. The percentage weight of pore distribution in the range of 45≥ ∅ <25 µm was 44.61%, indicated that to achieve an objective of NRC≥ 0.5 the most influential pore diameter range was 45≥ ∅ < 25.The increased number of jute fiber per unit area of felts from 55 to 430 resulted in narrowing of inter fiber spaces and consequently reduced the mean pore size. Further increase in number of fibers ultimately leads to blocking of spaces within fibers and get compacted like a solid fibrous mass.